Loss of PKD1 and loss of Bcl-2 elicit polycystic kidney disease through distinct mechanisms - Hughes, P (2005)
We have recently demonstrated that ablation of one or both alleles of the proapoptotic gene Bim prevents the polycystic kidney disease (PKD) that develops in mice deficient for the prosurvival protein Bcl-2. The aim of the present study was to investigate whether loss of Bim or Bcl-2 could influence the disease in the PKD1(del34/del34) mutant mice, a model of autosomal dominant PKD. PKD1(del34/del34) mice were intercrossed with Bim-deficient mice and Bcl-2(+/−) mice to generate double mutants. Loss of Bim does not prevent the development of PKD in PKD1(del34/del34) mice. On the C57BL/6 genetic background, most older PKD1(del34/+) mice do not develop PKD, but present with liver cysts. Surprisingly, loss of Bim completely prevented liver cysts formation in PKD1(del34/+) mice. Loss of one Bcl-2 allele did not influence the PKD1(del34) phenotype significantly. We conclude that loss of PKD1 and loss of Bcl-2 elicit PKD through distinct mechanisms.